Cultural Change in Post-Migrant Societies Re-imagining communities through arts and cultural activities - Sievers, Wiebke (2024)
The volume offers insights into new theoretical approaches that should make it possible to analyse cultural change through migration. It focuses on concrete activities in local contexts and their significance for national narratives. Finally, it presents newer approaches in migration studies that use artistic methods and work with cultural institutions to drive cultural change.